The effectiveness of education provided to university students on COVID-19 phobia: A quasi-experimental study - Kılınç, Nur Özlem; Uncu, Fatos; Güneş, Dilek; Kirkil, Gamze (My University, 2025)
This study aimed to determine the effectiveness of education provided to university students on COVID-19 phobia. The study was structured as a pre-test, post-test single-group study, a quasi-experimental research design, conducted on 122 students at a university located in Eastern Anatolia. Pre-test forms (Information Form, COVID-19 Phobia Scale) were sent to the students via email, filled out, and returned to the researcher. Subsequently, online training was provided to the participating students, and post-test (COVID-19 Phobia Scale) data were collected. A statistically significant difference was found between the pre-test and post-test COVID-19 Phobia Scale values (p<.001). This difference was in favor of the pre-test, indicating a reduction in COVID-19 phobia levels after the intervention. The results of this study highlight the importance of pandemic phobia and education. It provides data support for pandemic and COVID-19 phobia for policymakers, healthcare administrators, and the literature.
Keywords: Nurse; education; COVID-19 phobia; healthcare students